The Relationship Between Teacher Attitude Communication and Character Education of Tangerang City Junior High School Students - Lesmi, Kirana; Triono, Wahyu (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The purpose of the study was to obtain data related to 5 characteristics of teacher attitude communication in character education which include; (1) openness, (2) empathy, (3) Tangerang support, (4) positive Tangerang, and (5) equality. This study used descriptive quantitative method with survey technique with questionnaire instrument. The population of this study involved teachers from 3 public junior high schools in Tangerang City, totaling 137 people. Through the Slovin formula with an error of 0.5%, a sample of 102.00 was obtained, rounded up to 100 teachers who were taken randomly and proportionally. The results of the study are as follows; (1) teachers' openness in communicating with students is 51.50% which is included in the moderate category; (2) teachers' empathy in communicating with students is 49.00% which is included in the moderate category which tends to be less good; (3) teachers' supportive Tangerang in communicating with students is 51.50% which is included in the moderate category; (4) teachers' positive Tangerang in communicating with students is 50.00% which is included in the moderate category which tends to be less good; and (5) teachers' equality in communicating with students is 51.00% which is included in the moderate category. Then the accumulation of each aspect or indicator mentioned above obtained data showing that the teacher's communication ethics in student character education in public junior high schools in Tangerang City is 50.50%, including the moderate category.